Evaluation of prevalence and antibiogram of multi drug resistant, extensively drug resistant and pan drug resistant Pseudomonas aeruginosa in patients visiting a tertiary care hospital in central India - Gunjan Shrivastava; G S Bhatambare; K B Patel (Wolters Kluwer Medknow Publications, 2014)
Introduction: Antibiotic resistance is an increasing concern worldwide, specially in Gram negative bacilli where there is a paucity of new and effective antimicrobial agents. Pseudomonas aeruginosa is inherently resistant to different antimicrobial agents who are responsible for increase in morbidity and mortalities found in all types of patients. The purpose of this study was to evaluate the antibiogram of Multi drug resistant (MDR ), Extremely drug resistance (XDR) and Pan drug resistant (PDR) Pseudomonas aeruginosa. Aims and objectives: To find out the frequency and resistance pattern of MDR, XDR and PDR Pseudomonas aeruginosa. Materials and Methods: This is six month retrospective study, conducted in department of Microbiology a tertiary care hospital and teaching institute. During the study period (July-Dec 2013) routine samples were tested to standard microbiological procedure. Isolates were identified up to species level, Pseudomonas aeruginosa were picked up for further studies. Antibiotic sensitivity testing (AST) was performed by the Kirby-Bauer disc diffusion method, Carbapenemase production was screened by Hodge test and Modified Hodge test, extended spectrum beta lactamse (ESBL) production and AmpC presence were screened by two disc method. According to the sensitivity pattern, the strain was identified as MDR, XDR and PDR Pseudomonas aeruginosa. Results: During the study Pseudomonas aeruginosa were isolated from 198 (21.85%) samples. Among 198, 12 (6.06%) were identified as PDR, 23 (11.6%) were XDR whereas 49 (24.7%) were MDR. Out of 198, 98 (49.49%) were ESBL, 40 (20.20) were Carbapenemase producer and 4 (2.02) were AmpC producer. Conclusions: Though Pseudomonas aeruginosa is inherently resistance to different antimicrobial agents, irrational and inappropriate use of antibiotics is also responsible for the development of resistance to antibiotic. Hence, there is a need to emphasize the "rational drug" to minimize the misuse of antimicrobials. To minimize morbidity and mortalities due to Pseudomonas aeruginosa infection, prior AST is essential to provide specific treatment.